Pembuatan Biobriket dari Limbah Organik - Moh Syahri (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
The level of fuel consumption, especially of fossil fuels is increasing and becoming a major part in the industrial sector. Whereas fossil fuels is a resource that can be exhausted. And so we need alternative energy sources that can renewed, good for the environment and economic value. Organic waste has not been fully exploited, although organic waste such as durian skin waste, sawdust, corn cob and a biomass with relatively high calorific value. Alternative might be to manage organic waste into briquettes. Briquettes are Solid fuel made from organic waste in the pyrolysis and solidified. Bio-briquette-making process begins by draining waste durian skin, corn cobs, and sawdust, then in the pyrolysis by a tool pyrolysis (the retort). Bio char formed from the pyrolysis then crushed and sieved to a certain size. After it is mixed with a certain ratio and the added starch adhesive glue and printed with a press. The independent variables used in this study is a comparison of the composition of a mixture of durian skin charcoal, corn cob and sawdust that is 3: 2: 1, 3: 1: 2, 3: 3: 3 and pyrolysis time is 7 hours, 7.5 hours , and 8 hours and robust printing press briquettes are 50, 75 and 100 kg / cm2. Fixed and variable is the size of charcoal partiketie -30 + 50 mesh, 10% starch glue weight of the total weight, the pyrolysis temperature of 500 0C. The results showed that the highest calorific value obtained in the variable composition of 3: 1: 2 with 8 hours pyrolysis and print compressive strength of 100 kg / cm2 is 6960.5650 cal / g. And briquettes to meet the standard briquettes Japan, America, and Indonesia (SNI).